A political tsunami hits Amazon conservation. Issue 5 (26th March 2021) - Pelicice, Fernando Mayer; Castello, Leandro
Abstract: The history of conservation of the Amazon can be viewed as a war involving many battles with interests in agribusiness on one side and in biodiversity conservation and sustainability on the other side. Trends in large‐scale deforestation in the 1970s spurred a series of policies, stakeholder alliances and international and grass‐roots movements, which decades later led to the establishment of protected areas and interventions in soy and beef supply chains of agribusiness. Together, these advances epitomized a conservation framework for the Amazon, which at one point nearly curbed deforestation in the Brazilian Amazon, although it included very few protections for freshwater ecosystems. While those conservation advances were taking place, however, a series of policy changes started to undermine them through expansions in deforestation, river regulation and mining activities. The election of Brazil's President Jair Bolsonaro in 2019 then hit the Amazon conservation framework much like a tsunami of policy setbacks and the re‐establishment of the economic policies that sparked the Amazon war in the past. The current trajectory is one of large‐scale degradation of Amazonian ecosystems and biodiversity with consequent impacts on local people. Because freshwater ecosystems are highly sensitive to human activities on water and on land, these growing impacts are particularly large. It is too early to know, but four decades of institutional and policy developments to conserve the Brazilian Amazon may soon be pushed past the point from which they will be able to recover. Four conditions will be pivotal to allowing the Amazon conservation framework to recoup: (a) the end of Bolsonaro's mandate in 2022 or earlier; (b) remobilization of stakeholders; (c) investments in environmental research, policy and multiple collaborations; and (d) moving conservation beyond terrestrial landscapes to also encompass freshwater ecosystems and their people.